Dietary flavonoids prevent diabetes through epigenetic regulation: advance and challenge - Han, S.; Luo, Y.; Liu, B.; Guo, T.; Qin, D.; Luo, F.
The pathophysiology of diabetes has been studied extensively in various countries, but effective prevention and treatment methods are still insufficient. In recent years, epigenetics has received increasing attention from researchers in exploring the etiology and treatment of diabetes. DNA methylation, histone modifications, and non-coding RNAs play critical roles in the occurrence, maintenance, and progression of diabetes and its complications. Therefore, preventing or reversing the epigenetic alterations that occur during the development of diabetes may reduce the individual and societal burden of the disease. Dietary flavonoids serve as natural epigenetic modulators for the discovery of biomarkers for diabetes prevention and the development of alternative therapies. However, there is limited knowledge about the potential beneficial effects of flavonoids on the epigenetics of diabetes. In this review, the multidimensional epigenetic effects of different flavonoid subtypes in diabetes were summarized. Furthermore, it was discussed that parental flavonoid diets might reduce diabetes incidence in offspring, which represent a promising opportunity to prevent diabetes in the future. Future work will depend on exploring anti-diabetic effects of different flavonoids with different epigenetic regulation mechanisms and clinical trials. Highlightso "Epigenetic therapy" could reduce the burden of diabetic patientso "Epigenetic diet" ameliorates diabeteso Targeting epigenetic regulations by dietary flavonoids in the diabetes preventiono Dietary flavonoids prevent diabetes via transgenerational epigenetic inheritance.
Keywords: DIABETES; DIETARY FLAVONOIDS; EPIGENETICS; TRANSGENERATIONAL EPIGENETIC INHERITANCE